Data value chain in platform business models - Markéta Mlčúchová (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2022)
Building on a unified definition and the main attributes that have been identified for platform business models, this paper aims to devise a unified data value chain and shed a new light on the value creation process within platform business models. To meet the main aim of the paper, the following research question is addressed: 'How do platform business models create, deliver and capture value through their business model configurations?'. Through an integrative literature review, this paper confirmed that data is the major asset in value creation through platform business models. Furthermore, this paper has devised a unified data value chain that encom-passes sequential forms of digital data such as raw data, pre-processed data, processed data, patterns and smart data, gaining value via numerous processes throughout the data value chain. It was highlighted that interlinked processes throughout the data value chain transformed raw data into the most valuable form of data, knowledge.
Keywords: F23; M21; 330; Platform Business Model; Value Creation; Digital Data; Data Value Chain; Digitalisation